"Dear World Religions 101 Professor: Some Essentials About Non-Essentializing". Issue 2 (3rd April 2021) - Kuhlken, Pam Fox
Abstract: Thirty professors gathered for a 2017 National Endowment in the Humanities summer institute, "The Challenges of Teaching World Religions, " to confront complexities and nuances, hegemonies and political intrigue, hypocrisies and paradoxes–as these and other challenges play out in the present state of Religious Studies. This is the story of one participant's attempt to practically apply often abstract or esoteric expertise in the 101 classroom. Modern comparative religious study is modeled on biology, which presumes an unchanging essence. However, World Religions professors must accept that religions change and vary, so beyond the inception of founding texts and principles, in an existential sense, there is no stable essence in lived traditions. Therefore "religion" can never be essentialized into an undisputed whole, so "religions" should best be kept as a plural. As an example for World Religions pedagogy, NEH participants scrutinized blindspots that became visible with greater exposure to the diversity (political, historical, experiential, ritualistic, creedal) within each religious tradition, especially as they are actually practiced by various adherents, so hearing from a range of guest speakers, visiting sites, and using a range of World Religions textbooks modeled a twenty-first century pedagogy for teaching World Religions without the monocular "having the right answer" syndrome. Seeing religion not only as a path of wisdom, but also as an exercise of power, seminar participants examined the invisible assumptions of hegemonies, and made imaginative leaps to the experiential reality of selected world religions–all the while, having epistemological humility.